Long-term clinical course and treatment outcomes of individuals with Nodding Syndrome - Kegele, Josua; Wagner, Thomas; Kowenski, Teresa; Wiesmayr, Matthias; Gatterer, Christian; Alber, Michael; Matuja, Wiliam; Schmutzhard, Erich; Lerche, Holger; Winkler, Andrea S. (Journal of the neurological sciences, 2024)
Nodding Syndrome is a poorly understood epilepsy disorder in sub-Saharan Africa. The cause(s) of the disease, risk factors and long-term outcomes are unknown or controversial. The objectives of this study were to describe the long-term clinical course and treatment outcomes of individuals suffering from Nodding Syndrome. In addition, we aimed to provide a comprehensive characterization of the epileptological and social features of patients with Nodding Syndrome. From 11/2014 to 4/2015, we conducted a hospital-based, cross-sectional and observational study in Mahenge, Tanzania. Seventy-eight individuals (female:male ratio: 40:38, age at examination: 21.1 ± 6.39 (SD) years) have been enrolled, of whom 38 (49%) had also been examined in 2005 and in 2009. The 10-year clinical course analysis of this revisited subgroup revealed a calculated case fatality of 0.8-2.3%. Progressive physical or cognitive deterioration has not been observed in any of the 78 individuals and more than half of the people studied (38/69; 55%) managed to live and work independently. 14/78 individuals (18%) were seizure-free, (no head nodding, no other seizure types), 13 of whom were taking antiseizure medication. Phenytoin was more effective against head nodding seizures (14/19 (74%)) than monotherapy with other available antiseizure medication (phenobarbitone 12/25 (48%) and carbamazepine 7/22 (32%), p = 0.02, chi-square test). Our ten-year clinical outcome data show that Nodding Syndrome is not a fatal disease, however, the response to treatment is worse than in epilepsy patients in general. Phenytoin may be more effective than carbamazepine and phenobarbitone, but further studies are needed to confirm this observation.
Gesehen am 06.08.2024